(untitled) (Research, Society and Development, 2021)
The objective of the article is to describe how the processes of this neuropsychological influence the learning of reading of children with dyslexia, from a literature review on the subject. Along this path, various socioenvironmental influences related to specific difficulties in learning to read are examined, such as the education system and the social-family context. Thus, the work contributes academically to the understanding of the disorder, showing how biological, cognitive and social aspects interfere in the dyslexia process and emphasizing how a successful intervention depends on a careful and multidimensional evaluation of these factors related to developmental dyslexias.